Neural crest‐derived mesenchymal progenitor cells enhance cranial allograft integration. (29th January 2021) - Glaeser, Juliane D.; Behrens, Phillip; Stefanovic, Tina; Salehi, Khosrowdad; Papalamprou, Angela; Tawackoli, Wafa; Metzger, Melodie F.; Eberlein, Samuel; Nelson, Trevor; Arabi, Yasaman; Kim, Kevin; Baloh, Robert H.; et al.
Abstract: Replacement of lost cranial bone (partly mesodermal and partly neural crest‐derived) is challenging and includes the use of nonviable allografts. To revitalize allografts, bone marrow‐derived mesenchymal stromal cells (mesoderm‐derived BM‐MSCs) have been used with limited success. We hypothesize that coating of allografts with induced neural crest cell‐mesenchymal progenitor cells (iNCC‐MPCs) improves implant‐to‐bone integration in mouse cranial defects. Human induced pluripotent stem cells were reprogramed from dermal fibroblasts, differentiated to iNCCs and then to iNCC‐MPCs. BM‐MSCs were used as reference. Cells were labeled with luciferase (Luc2) and characterized for MSC consensus markers expression, differentiation, and risk of cellular transformation. A calvarial defect was created in non‐obese diabetic/severe combined immunodeficiency (NOD/SCID) mice and allografts were implanted, with or without cell coating. Bioluminescence imaging (BLI), microcomputed tomography (μCT), histology, immunofluorescence, and biomechanical tests were performed. Characterization of iNCC‐MPC‐Luc2 vs BM‐MSC‐Luc2 showed no difference in MSC markers expression and differentiation in vitro. In vivo, BLI indicated survival of both cell types for at least 8 weeks. At week 8, μCT analysis showed enhanced structural parameters in the iNCC‐MPC‐Luc2 group and increased bone volume in the BM‐MSC‐Luc2 group compared to controls. Histology demonstrated improved integration of iNCC‐MPC‐Luc2 allografts compared to BM‐MSC‐Luc2 group and controls. Human osteocalcin and collagen type 1 were detected at the allograft‐host interphase in cell‐seeded groups. The iNCC‐MPC‐Luc2 group also demonstrated improved biomechanical properties compared to BM‐MSC‐Luc2 implants and cell‐free controls. Our results show an improved integration of iNCC‐MPC‐Luc2‐coated allografts compared to BM‐MSC‐Luc2 and controls, suggesting the use of iNCC‐MPCs as potential cell source for cranial bone repair. Abstract : Bone marrow‐derived mesenchymal stromal cells (BM‐MSCs) were obtained from human bone marrow. Induced neural crest cell‐mesenchymal progenitor cells (iNCC‐MPCs) were generated from induced pluripotent stem cell‐derived iNCCs. Cells were luciferase transfected and seeded onto decellularized allografts, which were implanted into 5 mm circular calvarial defects in non‐obese diabetic/severe combined immunodeficiency (NOD/SCID) mice. Allograft only was used as controls. Mice were followed for a duration of 8 weeks. Cell survival, allograft integration, and tissue morphology and transplanted cell contribution were monitored via bioluminescence imaging (BLI), micro‐computed tomography (μCT), and histology and immunofluorescence (IF). Green arrow: BLI; yellow arrow: μCT; Orange arrow: histology and IF; Blue arrow: biomechanical test.